Increasing cotton lint yield and water use efficiency for subsurface drip irrigation without mulching - Li, Nan-nan; Li, Jun-hong; Shi, Xiao-juan; Shi, Feng; Tian, Yu; Wang, Jun; Hao, Xian-zhe; Luo, Hong-hai; Wang, Zhan-biao (Frontiers in Plant Science, 2024)
Planting without mulching can eliminate the residual film pollution caused by the long-term use of plastic film covers, but it will increase soil moisture evaporation and heat loss and severely reduce water use efficiency and cotton productivity in cotton (Gossypium hirsutum L.) fields in arid regions.It is unclear whether the advantages of subsurface drip irrigation and nighttime irrigation can be leveraged to reduce the amount of irrigation applied in fields, improve the soil and leaf hydrothermal environments, and increase the synchronicity of yield and water use efficiency (WUE). Therefore, in a two-year field experiment (2019-2020), cotton was grown under different irrigation treatments (I5, 3753 m 3 ha -1 ; I4, 3477 m 3 ha -1 ; I3, 3201 m 3 ha -1 ; I2, 2925 m 3 ha -1 ; and I1, 2649 m 3 ha -1 ). The soil volumetric moisture content, soil temperature, leaf relative water content (RWC), daily changes in gas exchange parameters, lint yield, and WUE were evaluated. The results showed that reducing irrigation can reduce the soil volumetric moisture content (0-40 cm soil layer), increase the soil temperature and soil temperature conductivity, and increase the leaf temperature, intercellular carbon